Technical Teachers Training Institute, Bhopal - Soni, S. K. (Journal of Engineering Education Transformations, 1998)
Govt. of India established four Technical Teachers’ Training Institutes in the country in 1965. For Western region the institute was located at Bhopal. It initially started functioning in the premises of S. V. Polytechnic Bhopal. In 1977 it had its own campus. Fig 1.1 shows jurisdiction of this regional institute and details of each state. Fig 1.2 depicts organizational structure. Through the years of working with the state system TTTI Bhopal has believed ill project approach. Interdisciplinary task group structure is evolved for effective functioning. Project approach ensures visible outcome and impact on the system. Recognizing the need and importance of highly qualified resource persons in the educational field TTTI Bhopal designed and started Masters Programme in Technical Education [M.Tech. (Ed.)] ill 1986 which is approved by Govt. of India and AICTE. This is the unique programme in the country. Many states (even outside the region) are taking advantage of the M.Tech. (Ed.) programme. In 1991, Govt. of India launched World Bank Assisted Project for the development of Technician Education System in the country. The institute was actively involved in preparation of the project at national level. For smooth functioning matrix structure was introduced to account for project components and departmental structure. Fig. 1.3 shows Matrix Structure. We received a questionnaire from the editor and responses have been provided in detail. These responses ’would reveal our contributions and our future perspective.